Prediction of angiogenesis suppression by myricetin from Aeginetia indica via inhibiting VEGFR2 signaling pathway using computer-aided analysis - Marjanur Rahman Bhuiyan; Khondoker Shahin Ahmed; Md Sharif Reza; Hemayet Hossain; Syed Mumtahin Mannan Siam; Shahriar Nayan; Sarah Jafrin; Sadikur Rahman Shuvo; A.F.M.Shahid Ud Daula (Heliyon)
Vascular endothelial growth factor receptor-2 (VEGFR2) plays a pivotal role in promoting angiogenesis and contributing to the growth and progression of renal cancer. Hence, the current investigation was undertaken with the aim of identifying safe and potent phytochemicals from Aeginetia indica whole plant extract (AiWE) that can efficiently suppress the overexpression of VEGFR2. HPLC analysis identified and quantified 11 polyphenols in considerable amounts in AiWE. All the compounds showed good binding energies with VEGFR2 in the molecular docking study, except catechin hydrate and rutin hydrate. However, among the polyphenols, myricetin exhibited an almost similar hydrogen bonding pattern with the active site of VEGFR2. The all-atom molecular dynamic simulation revealed that myricetin showed a very stable interaction with the active site of VEGFR2 throughout the simulation. Based on these results, it is suggested that myricetin may inhibit angiogenesis by suppressing the VEGFR2 signaling, thereby impeding the growth and progression of renal cancer.